2016
DOI: 10.1155/2016/1230384
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Back Pain among Undergraduate Physiotherapy Students in Nigeria

Abstract: Background. Low back pain (LBP) is a major cause of disability and the most common work-related musculoskeletal disorder among physiotherapists. This study examined the prevalence of low back pain among students undergoing training to become physiotherapists. Methods. Participants were 207 undergraduate clinical physiotherapy students at three universities in Nigeria. A modified version of a questionnaire used in a previous study was utilized to obtain demographic, educational activities, and LBP data. Prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…This mismatch is likely to cause hip and back pains among students as indicated in the study by Kumar,[20]. Second, insufficient lumbar support results in sitting with a round back, which if prolonged have been known to cause non-specific low back pain [5]. Finally, poor desk to seat ratiocreates an uncomfortable distance between the seat and desk, forcing the student to lean forward in attempt to use the desk, sustained usage in this position often results in forward head posture [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This mismatch is likely to cause hip and back pains among students as indicated in the study by Kumar,[20]. Second, insufficient lumbar support results in sitting with a round back, which if prolonged have been known to cause non-specific low back pain [5]. Finally, poor desk to seat ratiocreates an uncomfortable distance between the seat and desk, forcing the student to lean forward in attempt to use the desk, sustained usage in this position often results in forward head posture [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, students are prone sitting on the edge of the chair to assess the table as a result of increased length between the seat and desk [21]. Absence of lumbar support also resulted in sitting with a round back and have been known to cause muscle imbalance with a number of other lower and upper back issues [5,26]. Notably, the furniture in both faculties lack flexibility, since the desks are permanently attached to the chairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specific low back pain (NSLBP) is a major global burden indiscriminately affecting all people including physiotherapists [ 1 9 ]. Physiotherapists are at an increased risk of developing NSLBP due to the physical demands of the profession [ 7 , 10 15 ]. This is despite physiotherapists having expert knowledge about injury prevention from training [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have reported varying prevalence rates for NSLBP among physiotherapy students with lifetime prevalence figures ranging between 36 and 69% [ 7 , 10 , 12 , 17 ]. Also, Nyland and Grimmer [ 12 ] reported a 12-month prevalence of 63% in Australia.…”
Section: Introductionmentioning
confidence: 99%